Shared sources and mechanisms of healthcare worker distress in COVID-19: a comparative qualitative study in Canada and the UK. Issue 2 (19th December 2022) - Berkhout, Suze G.; Billings, Jo; Abou Seif, Nada; Singleton, David; Stein, Hilarie; Hegarty, Siobhan; Ondruskova, Tamara; Soulios, Emilia; Bloomfield, Michael A.P.; Greene, Talya; Seto, Alison; Abbey, Susan; et al.
ABSTRACT: Background: COVID-19 has had a significant impact on the wellbeing of healthcare workers, with quantitative studies identifying increased stress, anxiety, depression, insomnia, and PTSD in a wide range of settings. Limited qualitative data so far has offered in-depth details concerning what underlies these challenges, but none provide comprehensive comparison across different healthcare systems. Objective: To explore qualitative findings relating to healthcare worker distress from two different countries to understand the nuanced similarities and differences with respect to the sources and impact of distress relating to COVID-19. Method: A comparative interpretive thematic analysis was carried out between two qualitative data sets examining healthcare workers' experiences of distress during the COVID-19 pandemic. Data from Canada and the UK were collected in parallel and analyzed in an iterative, collaborative process. Results: A number of sources of distress cut across both study settings including concerns about safety and patient care, challenges at home or in one's personal life, communication issues, work environment, media and public perception, and government responses to the pandemic. These sit on a spectrum from individual to institutional sources and were mutually reinforcing. Our analysis also suggested that common mechanisms such as exacerbations in uncertainty, hypervigilance, and moral injury underpinned these sources, which contributed to how they were experienced as distressing. Conclusion: This is the first international collaboration utilising qualitative data to examine this pressing issue. Despite differences in the political, social, health service, and pandemic-related context, the sources and mechanisms of distress experienced by healthcare workers in Canada and the UK were remarkably similar. HIGHLIGHTS This international comparative qualitative study explores how mechanisms that lead to distress are shared across different geographies and cultures, even as the local context shapes the sources of distress themselves.